Designing for Privacy and its Legal Framework Data Protection by Design and Default for the Internet of Things - Tamò-Larrieux, Aurelia (Issues in Privacy and Data Protection,, 2018)
This book discusses the implementation of privacy by design in Europe, a principle that has been codified within the European Data Protection Regulation (GDPR). While privacy by design inspires hope for future privacy-sensitive designs, it also introduces the need for a common understanding of the legal and technical concepts of privacy and data protection. By pursuing an interdisciplinary approach and comparing the problem definitions and objectives of both disciplines, this book bridges the gap between the legal and technical fields in order to enhance the regulatory and academic discourse. The research presented reveals the scope of legal principles and technical tools for privacy protection, and shows that the concept of privacy by design goes beyond the principle of the GDPR. The book presents an analysis of how current regulations delegate the implementation of technical privacy and data protection measures to developers and describes how policy design must evolve in order to implement privacy by design and default principles.